Nuclear Transport of the Major Capsid Protein Is Essential for Adeno-Associated Virus Capsid Formation - Hoque, Mainul (American Society for Microbiology, 1999)
Adeno-associated virus capsids are composed of three proteins, VP1, VP2, and VP3. Although VP1 is necessary for viral infection, it is not essential for capsid formation. The other capsid proteins, VP2 and VP3, are sufficient for capsid formation, but the functional roles of each protein are still not well understood. By analyzing a series of deletion mutants of VP2, we identified a region necessary for nuclear transfer of VP2 and found that the efficiency of nuclear localization of the capsid proteins and the efficiency of virus-like particle (VLP) formation correlated well. To confirm the importance of the nuclear localization of the capsid proteins, we fused the nuclear localization signal of simian virus 40 large T antigen to VP3 protein. We show that this fusion protein could form VLP, indicating that the VP2-specific region located on the N-terminal side of the protein is not structurally required. This finding suggests that VP3 has sufficient information for VLP formation and that VP2 is necessary only for nuclear transfer of the capsid proteins.